Productivity and profitability of aerobic rice (Oryza sativa) as influenced by varieties and integrated nitrogen management - SHARMA, S K; TYAGI, SURUCHI; SINGH, Y V; TOMAR, B S; SINGH, K K (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during the kharif seasons of 2009 and 2010 at Indian Agricultural Research Institute, New Delhi to study productivity and profitability of aerobic rice as influenced by varieties and integrated nitrogen management. The experimental treatments included 2 rice varieties, viz. Pusa Basmati 1 and Pusa Basmati 1121 and 8 integrated nitrogen management practices, viz. N control (N0); 100% RDN (120 kg N/ha through urea); 75% RDN + 25% N through farmyard manure; 75% RDN + 25% N through green manuring; 75% RDN + 25% N through biofertilizers; 75% RDN + 25% N through vermicompost; 100% N through FYM+GM+BF+VC and 100% N through FYM+GM+BF+VC+ZnSO4. The results showed that rice variety Pusa Basmati 1 out performed Pusa Basmati 1121 in yield attributes, grain yield and harvest indices. Application of recommended dose of nitrogen (RDN) through integrated nitrogen management (INM) approach significantly increased the crop growth parameters, yield attributes, grain as well straw yields and net returns over other INM approaches. Treatment with 100% N by FYM+GM+BF+VC+Zn showed highest crop growth and yield attributes, grain and straw yield and net returns as compared to other integrated nitrogen management treatments, but this treatment was closely followed by 100% N by FYM+GM+BF+VC and 75% RDN + 25% VC during both the years.